Clinacanthus nutans aqueous extract exerts anti-allergic activity in preclinical anaphylactic models via alternative IgG pathway - Kow, Audrey Siew Foong; Khoo, Leng Wei; Tan, Ji Wei; Abas, Faridah; Lee, Ming-Tatt; Ahmad Israf, Daud; Shaari, Khozirah; Tham, Chau Ling (Elsevier Ireland, 2023)
Ethnopharmacological relevance Allergy is mediated by the crosslinking of immunoglobulins (Ig) -E or -G to their respective receptors, which degranulates mast cells, macrophages, basophils, or neutrophils, releasing allergy-causing mediators. The removal of these mediators such as histamine, platelet-activating factor (PAF) and interleukins (ILs) released by effector cells will alleviate allergy. Clinacanthus nutans (C. nutans), an herbal plant in Southeast Asia, is used traditionally to treat skin rash, an allergic symptom. Previously, we have reported that C. nutans aqueous leaves extract (CNAE) was able to suppress the release of β-hexosaminidase and histamine but not interleukin-4 (IL-4) and tumor necrosis factor-alpha (TNF-α) in the IgE-induced mast cell degranulation model at 5 mg/mL and above. We also found that CNAE could protect rats against ovalbumin-challenged active systemic anaphylaxis (OVA-ASA) through the downregulation and upregulation of certain metabolites using proton nuclear magnetic resonance (1H-NMR) metabolomics approach.